2017
DOI: 10.1016/j.ajog.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and management of vasa previa in twin pregnancies: a case series and systematic review

Abstract: Word count: 3208Condensation: Management strategies in twin pregnancies presenting with vasa praevia should be tailored on the basis of chorionicity and changes in cervical length. Short title: Management of vasa previa in twinsKey Words: Velamentous; umbilical cord; vasa previa; twins; placenta. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 45 publications
(71 reference statements)
2
35
0
Order By: Relevance
“…From 2008, all asymptomatic women presenting with VP were followedup with transvaginal ultrasound for cervical length and VP position every 2 weeks from the time of the first diagnosis of VP until delivery. 17 The timing of delivery was scheduled according to changes in cervical length and/or clinical symptoms (mainly uterine contractions and/or vaginal bleeding), following a course of corticosteroids.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From 2008, all asymptomatic women presenting with VP were followedup with transvaginal ultrasound for cervical length and VP position every 2 weeks from the time of the first diagnosis of VP until delivery. 17 The timing of delivery was scheduled according to changes in cervical length and/or clinical symptoms (mainly uterine contractions and/or vaginal bleeding), following a course of corticosteroids.…”
Section: Methodsmentioning
confidence: 99%
“…When the cervical remains stable with normal fetal development and there are no clinical symptoms delivery was planned at 35-36 weeks' gestation. 17 Before implementation of the scanning protocols, cases had to be recovered from medical records whereas all cases post-implementation of the protocols were…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, data from a 2017 systematic review on the management of vasa praevia in twins have indicated that TVS cervical length measurements from 26-28 weeks of gestation may be useful to evaluate the individual risk of preterm birth. 34…”
mentioning
confidence: 99%
“…When first received, it is important to be able to identify the twins; while in theory, the first delivered twin (twin 1) and second delivered twin (twin 2) can be identified from examination of the membranes [the opening from the sac of twin 1 will be through the free membranes, while the opening from the sac of twin 2 will be through the dividing membrane into the sac of twin 1], the frequency of Cesarean section and of artifactual tearing of the membranes makes it more reliable to have an agreed cord labeling protocol with the local obstetricians. As the frequency of velamentous cord insertion and vasa previa is increased in twin pregnancy , the initial examination of the membranes should carefully document velamentous cord insertions and document by photography whether vessels running through membranes are intact or otherwise, especially when they run close to the membrane rupture site. If velamentous vessels are disrupted, it is prudent to determine if there was any clinical evidence of fetal hemorrhage from vasa previa; in these cases, gross photography is the most valuable method to document the ruptured vessel, its relationship with the membrane opening, and any hemorrhage into adjacent membranes.…”
Section: Initial Evaluationmentioning
confidence: 99%